Infection Prevention And Control In Nursing Practice: Strategies, Challenges, And Innovations (The Review of Diabetic Studies, 2025)
Background: Infection prevention and control (IPC) is a fundamental component of nursing practice and patient safety. Despite global efforts, healthcare-associated infections (HAIs) remain a major cause of morbidity, mortality, and financial strain. Nurses are pivotal in implementing IPC measures that reduce infection risks and promote quality care across healthcare settings.Methods: This review synthesizes evidence from the World Health Organization (WHO), Centers for Disease Control and Prevention (CDC), and recent research to evaluate nursing-led IPC strategies. The analysis applies theoretical and behavioral frameworks such as the Chain of Infection, Donabedian Model, and COM-B to explore factors influencing IPC effectiveness.Results: Effective IPC interventions, including hand hygiene, personal protective equipment (PPE) use, environmental cleaning, and antimicrobial stewardship, can prevent up to half of all HAIs. However, implementation is often limited by resource constraints, staffing shortages, and behavioral barriers. Educational innovations, such as simulation training and e-learning, enhance competence and compliance, while emerging technologies, including automated disinfection, electronic surveillance, and AI-based analytics, strengthen infection monitoring and prevention.Conclusions: Nursing-led IPC programs are critical for safe and sustainable healthcare. Strengthening education, leadership, and institutional support can bridge gaps between knowledge and practice. Future priorities include integrating digital tools, fostering behavioral change, and embedding IPC into nursing policy and curricula to ensure preparedness against current and emerging infectious threats.